2004
DOI: 10.1128/jcm.42.10.4726-4734.2004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Secretory Aspartyl Proteinase Genes ( SAP1 - 10 ) in Oral Candida albicans Isolates with Distinct Karyotypes

Abstract: Two karyotypes of oral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…However, cross-sectional studies of C. albicans SAP gene expression in human OPC showed that SAP2, as well as SAP4 to SAP6, were predominantly expressed in OPC patients, as well as Candida carriers (5,(13)(14)(15)(16). C. albicans recovered from murine OPC showed that Sap4 to -6 were highly expressed during infection; however, other studies found a role for Sap1 to -6 in fungal invasion and damage to oral and vaginal epithelial mucosal surfaces (5,14,(16)(17)(18)(19)(20)(21). Thus, functional analyses of the abilities of individual Saps to promote virulence in mucosal infection has been inconclusive, due to different expression levels during the course of infection.…”
mentioning
confidence: 99%
“…However, cross-sectional studies of C. albicans SAP gene expression in human OPC showed that SAP2, as well as SAP4 to SAP6, were predominantly expressed in OPC patients, as well as Candida carriers (5,(13)(14)(15)(16). C. albicans recovered from murine OPC showed that Sap4 to -6 were highly expressed during infection; however, other studies found a role for Sap1 to -6 in fungal invasion and damage to oral and vaginal epithelial mucosal surfaces (5,14,(16)(17)(18)(19)(20)(21). Thus, functional analyses of the abilities of individual Saps to promote virulence in mucosal infection has been inconclusive, due to different expression levels during the course of infection.…”
mentioning
confidence: 99%
“…Regardless of the site of isolation, Sap 2 has been shown to be preferentially expressed by yeast-forming fungi in media containing bovine serum albumin as the protein substrate (14). Among the enzymatic properties of Sap 2 described in the literature, the proteolysis of collagen (30), the decreased efficiency of phagocytosis by polymorphonuclear neutrophils (3), and the activation of the proinflammatory cytokine interleukin-1 beta (31, 32) may contribute to bone resorption in the periapex, thus playing an important role in the onset and progression of apical periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies (2,6,14,16) have emphasized that the ability to degrade protein substrates is an important contribution to the establishment of C. albicans infections in various organic environments. Specifically, the increased proteolytic activity among strains isolated from necrotic root canals suggests that these microorganisms can participate in establishing and maintaining endodontic infections although this remains to be shown experimentally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mendes et al (2007) showed that biofilms of C. albicans consistently secrete more Saps than their planktonic counterparts, suggesting that increased Sap production is yet another mechanism by which yeasts persist on host surfaces, in addition to the expression of the foregoing virulence attributes. Another intriguing observation is that the Sap-encoding genes SAP1-10 were differentially expressed in C. albicans oral isolates that possess distinct genome backgrounds, referred to as b and c karyotype profiles, in which the c karyotype express a higher number of SAP1-10 genes than b-type strains during their in vitro propagation (Tavanti et al 2004). The host immune system is the major factor determining whether this opportunistic yeast behaves as a commensal or as a pathogen.…”
Section: Candida Sppmentioning
confidence: 98%